The Impact of the Method of Dealing with the Product of Wars in the Continuity of the Crisis Wars. Beirut city as an Example (Journal of Planner and Development, 2020)
This research investigates the subject of the impact of wars (as a manifestation of crisis) on architecture, and the extent of continuing wars physical and moral results of wars, even after the end of the cause of the crisis. The impact of different rebuilding which exposed to the effects of the war seems different in crisis regions. The problem of research is about the uncertainty of the impact of the way chooses for reconstructing the buildings after wars in the continuity of the crisis of war. The goals of this research are to clarify the influence of methods of reconstruction of buildings in a city chosen which is Beirut, on the continuation of the war crisis with the argument of demolishing and rebuilding newly or keeping traces of war. Main concepts, methods, and studies of wars’ crisis have been reviewed. The case study includes two buildings, which are located on both sides of contactless civil war in Beirut line. Two approaches of renewing these building have been adopted. It has come in the most important conclusions, that the selection of the way of the reconstruction of post-war buildings. In the first case, the method has used to rehabilitate the building structure to keep the impact of the crisis as it is to survive the war’s memory. In the second building, the used method was totally demolish the whole building and rebuilt a new one in order to remove all connections from the effects of the crisis war. The reconstruction has produced new crises and caused the continuation of the crisis linked to the original one.